Bioethics and Sanctity of Life: Kantian and Catholic Perspectives on Human Dignity in Vaccines Technology - Wekesa, Oliver Barasa (Université d'Ottawa | University of Ottawa, 2023)
Diverse and sometimes contradictory statements in the media by bishops, Catholic organizations, and experts have raised concerns about the morality of Covid-19 vaccines. This paper will first show that the Church has been inconsistent on the moral permissibility of using Covid-19 vaccines. The Catholic Church has not been speaking in one voice concerning the Covid-19 pandemic, especially its moral and ethical aspects; even when it was confirmed that some of the vaccines offered had used aborted cell lines in their research, production, and manufacture. On December 21, 2020, the Congregation for the doctrine of faith (CDF) observed that "…diverse and sometimes conflicting pronouncements in the mass media by cardinals, bishops, catholic institutions or associations, and experts have raised questions about the morality of the use of Covid-19 vaccines” (Congregation for the Doctrine of Faith). Such a statement raises the question of why there is no agreement among the Catholic magisterium on the Covid-19 vaccines, which the Pope has deemed licit. Pope Francis, through the Congregation for the doctrine, taught that "If ethically sound Covid-19 vaccines are not available, for example, in countries where ethically unproblematic vaccines are not provided to doctors or patients, or where their distribution proves more difficult due to special storage or transport conditions, or if different types of vaccines are distributed in the same country but health authorities do not let citizens decide which vaccine they be vaccinated with, it is therefore morally permissible to receive vaccinations against Covid-19, which have used cell lines from aborted fetuses in their development and manufacture (Congregation for the Doctrine of Faith). So it is discouraging to perceive contradictory messages from the magisterium regarding the Covid-19 pandemic, especially on the part of vaccinations. As mentioned above, some church authorities have permitted their use, and some have not. I will resolve this by taking the side against their use by arguing that it is immoral to use Covid-19 vaccines that have been developed using fetal cells. I will argue that a fetus is a person right from conception and thus should be accorded dignity. As a result, harvesting cell lines from elective abortion for producing or testing Covid-19 vaccines is morally wrong. This study will look at Kantian and Catholic Church teaching on the dignity and sanctity of the human person. The study will also provide a background and statement of the problem, the epidemiology and science of Covid-19 vaccines, bioethical principles from the perspective of the Catholic Church, a personal critique, and a conclusion.